Religious Tolerance: A Weapon Against Radicalism Due To The Impact of Artificial Intelligence (AI) - Fauzi Ridhallah; Efendi Efendi; Zaim Rais; Quratul Aini (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
Radicalism is a big problem that hits the current condition. Almost every region and place experience this problem. There are many factors that cause radicalism to appear, one of which is the development of technology such as Artificial Intelligence (AI), although this problem does not necessarily disappear just like that, but there needs to be an attitude to suppress this problem, namely is to give rise to various tolerance attitudes which can reduce and even kill the problem of radicalism. In the research, the researcher uses the literature study method by digging for information and analyzing various sources to offer solutions to this problem of radicalism. The purpose of this research is to seek to find the impact of the influence of Artificial Intelligence (AI) technology on the problem of radicalism and offer solutions related to this problem. Obtaining information from researchers to gain religious tolerance can suppress the development of radical ideas caused by Artificial Intelligence (AI)